Vaccinations against infuenza of healthcare workers - Topczewska, Katarzyna; Stecko, Monika; Stangret, Anna; Mularczyk, Agata (Journal of Education, Health and Sport, 2018)
Flu is a contagious disease that poses a problem recurring in each influenza season with varying intensity. At the end of the XX and early XXI century new subtypes appeared , which indicates the high variability of the pathogen from the moment of its isolation to the present day. Many people do not realize, how big a threat is flu, its consequences have a significant rebound in both the health and economic sphere. On the issue of influenza, the best prevention measure is prophylaxis. Hygiene behaviour meet with approval and the problem of incorporating these behaviours into life, while the most effective way of preventing influenza in the form of vaccination, for unknown reasons, does not enjoy excessive recognition and good reputation among the population. Medical personnel through frequent and close contact with patients are exposed to various pathogens that cause disease. The increase in influenza flu among medical personnel facilitates the transmission of a disease that is spreading among patients and other employees. This creates a significant coordination problem, associated with the need to deal with staff shortages among employees, mainly during the epidemic seasons typical of influenza. The results of serological tests show that seasonal exposure to influenza virus is about 25% of medical workers [1].